Kesan Beberapa Parameter Fisikal ke atas Tindak Balas Esterifikasi oleh Lipase Miselium daripada Rhizopus oryzae - Salleh, Abu Bakar; Abdul Razak, Che Nyonya; Ampon, Kamaruzaman; Wan Yunus, Wan Md Zin (Universiti Putra Malaysia Press, 1995)
Some physical parameters for the esterification of oleic acid and butanol by mycelial lipase from Rhizopus oryzae were examined. The enzyme can be used in the powder or fragment form, and the reaction proceeds without the need for shaking. The rate of esterification increases with the amount of enzyme up to 80% conversion, the maximum conversion achieved in 24 h. The optimum temperature of the reaction is 40°C, but the enzyme is stable up to 70°C. The enzyme is active in organic solvents with high log P values. The enzyme is also stable when stored in hexane.